Global business leadership development for the fourth industrial revolution - Smith, Peter (Leadership Alliance Inc., Canada); Cockburn, Tom, 1949- (Advances in business strategy and competitive advantage., 2020)
"This book explores the latest research and best practices regarding emergent digital technologies in global business"--